2011
DOI: 10.1016/j.freeradbiomed.2011.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of the antibacterial precursor thiocyanate in cystic fibrosis airway secretions

Abstract: A recently discovered enzyme system produces antibacterial hypothiocyanite (OSCN − ) in the airway lumen by oxidizing the secreted precursor thiocyanate (SCN − ). Airway epithelial cultures have been shown to secrete SCN − in a CFTR-dependent manner. Thus, reduced SCN − availability in the airway might contribute to the pathogenesis of cystic fibrosis (CF), a disease caused by mutations in the CFTR gene and characterized by an airway host defense defect. We tested this hypothesis by analyzing the SCN − concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 48 publications
(71 reference statements)
1
79
0
1
Order By: Relevance
“…Blood (8 ml) was drawn from the external jugular vein, and serum was collected. Nasal secretions were collected with microsampling probes (BC-402C; Olympus, Center Valley, PA) as previously described (24,32). Nasal fluid was recovered from the microsampling probes by microcentrifugation.…”
Section: Concentration Measurements In Airway Secretions and Serummentioning
confidence: 99%
See 2 more Smart Citations
“…Blood (8 ml) was drawn from the external jugular vein, and serum was collected. Nasal secretions were collected with microsampling probes (BC-402C; Olympus, Center Valley, PA) as previously described (24,32). Nasal fluid was recovered from the microsampling probes by microcentrifugation.…”
Section: Concentration Measurements In Airway Secretions and Serummentioning
confidence: 99%
“…Nasal fluid was recovered from the microsampling probes by microcentrifugation. Serum samples and nasal secretions were diluted in water and analyzed for anion composition using ionexchange chromatography as described previously (24,32).…”
Section: Concentration Measurements In Airway Secretions and Serummentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, CFTR is also a major characterized apical transporter of SCN in the airway (46). Some studies have found decreased SCN in CF secretions and positively correlated SCN levels with lung function (17,41,47). Because even small changes in SCN concentration can dramatically affect the oxidant production of MPO and other haloperoxidases (3), deficient apical SCN transport could dramatically change the outcomes of infection and inflammation in the airway by shifting toward HOCl production, resulting in worse tissue inflammation and injury.…”
Section: The Conserved Active Sequence Of H-trxr and Gr (Cvn-vgc) Locmentioning
confidence: 99%
“…However, it is clear from this work that urate and thiocyanate should be considered as competing physiological substrates for LPO. They are present in airway lining fluids at largely varying concentration ranges (urate: 40 -370 M, thiocyanate: 50 -400 M) (19,69), so they will compete for oxidation by compound I. It is likely that under most circumstances thiocyanate is the preferred substrate for compound I and urate will act simply by preventing accumulation of compound II and maintaining production of hypothiocyanite.…”
mentioning
confidence: 99%